Antibiotic-Resistant Urinary Tract Infection in a Bahamian Woman: A Case Report - L. Rivers, Keith (Journal of Clinical Case Reports and Images, 2025)
Bacterial resistance to antibiotics is becoming a major public health challenge in the Bahamas. Indiscriminate use of antibiotics by medical practitioners is a major contributor to this problem. We describe a 53-year-old woman who presented with symptoms of a urinary tract infection. Empiric treatment with first- and second-line antibiotics, namely trimethoprim-sulfamethoxazole and ciprofloxacin, respectively, were ineffective in clearing the infection. After culture and sensitivity testing via minimum inhibitory concentration analysis, nitrofurantoin proved to be the only effective oral antibiotic.
Keywords: Antibiotic-resistant; urinary tract infection; Treponema pallidum